Production of cyclodextrin (cd) using immobilized recombinant Escherichia coli - Rohaida, Che Man; Nurul Nabila Huda, Baharudin; Nur Nadia, Mohd Zakaria; Zatul Iffah, Mohd Arshad; Siti Zubaidah, Sulaiman (2021)
Cyclodextrin glucanotransferase (CGTase) + starch  CD. Nontoxic compound – capable to form molecular inclusion complexes. Soluble in water.